Uneventful COVID-19 Infection and Vaccination in a Cohort of Patients with Prior Myocarditis - Anna Baritussio; Andrea Silvio Giordani; Cristina Basso; Cristina Vicenzetto; Giulia Lorenzoni; Matteo Gasparin; Sabino Iliceto; Bruno Scarpa; Dario Gregori; Renzo Marcolongo; Alida Linda Patrizia Caforio (Vaccines, 2023)
Myocarditis has in rare cases been associated with COVID-19 infection and has emerged as a possible rare side effect of vaccination with anti-COVID-19 messenger RNA vaccines. However, little is known about possible COVID-19 infection- and/or vaccination-related myocarditis relapse in patients with previous clinically suspected or biopsy-proven myocarditis. Myocarditis may relapse, particularly in females with immune-mediated/autoimmune features and a predisposing immunogenetic background. We aimed to assess the prevalence of myocarditis relapse during the COVID-19 outbreak and following COVID-19 vaccination in a cohort of patients with prior myocarditis. We included in the analysis myocarditis patients on active follow-up, for whom COVID-19 infection and vaccination statuses were known, and collected data on clinical, laboratory and echocardiographic findings, and myocarditis relapse. We enrolled 409 patients, of whom 114 (28%) reported COVID-19 infection and 347 (85%) completed the vaccination scheme. Only one patient, having COVID-19 infection before the vaccination campaign started, was admitted to hospital because of pneumonia; the remaining patients had an uneventful COVID-19 infection course, with only mild symptoms. No myocarditis relapse was recorded following COVID-19 infection or vaccination. Moreover, the frequency of new myocarditis cases following the COVID-19 outbreak was not different compared to the three-year period preceding the COVID-19 era. In conclusion, in our cohort of patients with prior myocarditis, both COVID-19 infection and vaccination were uneventful.